Platelets, extracellular vesicles and coagulation in pulmonary arterial hypertension. (June 2021) - Cullivan, Sarah; Murphy, Claire A.; Weiss, Luisa; Comer, Shane P.; Kevane, Barry; McCullagh, Brian; Maguire, Patricia B.; Ní Ainle, Fionnuala; Gaine, Sean P.
Pulmonary arterial hypertension is a rare disease of the pulmonary vasculature, characterised pathologically by proliferation, remodelling and thrombosis in situ . Unfortunately, existing therapeutic interventions do not reverse these findings and the disease continues to result in significant morbidity and premature mortality. A number of haematological derangements have been described in pulmonary arterial hypertension which may provide insights into the pathobiology of the disease and opportunities to explore new therapeutic pathways. These include quantitative and qualitative platelet abnormalities, such as thrombocytopaenia, increased mean platelet volume and altered platelet bioenergetics. Furthermore, a hypercoagulable state and aberrant negative regulatory pathways can be observed, which could contribute to thrombosis in situ in distal pulmonary arteries and arterioles. Finally, there is increasing interest in the role of extracellular vesicle autocrine and paracrine signalling in pulmonary arterial hypertension, and their potential utility as biomarkers and novel therapeutic targets. This review focuses on the potential role of platelets, extracellular vesicles and coagulation pathways in the pathobiology of pulmonary arterial hypertension. We highlight important unanswered clinical questions and the implications of these observations for future research and pulmonary arterial hypertension-directed therapies.